Moisture dynamics in wall paintings monitored by single‐sided NMR1. (29th October 2014) - Oligschläger, D.; Waldow, S.; Haber, A.; Zia, W.; Blümich, B.; Capitani, Donatella; Proietti, Noemi
<x xml:space="preserve">Abstract</x> The durability of historic wall paintings is highly dependent on environmental influences such as moisture ingress, salt crystallization and temperature changes. A fundamental understanding of dynamic transport processes in wall paintings is necessary to apply suitable conservation and restoration methods to preserve such objects with high cultural value. Non‐invasive, mobile‐NMR techniques with single‐sided sensors, such as the NMR‐MOUSE®, enable to monitor the moisture content, transport and apparent diffusion constants in wall paintings. We investigated this technique by experiment and modeling to correlate salt crystallization, moisture transport and local diffusion in wall‐painting samples. Moreover, the influence of different painting techniques (fresco and secco) and conservation/consolidation methods on moisture transport and diffusion is discussed. The results are compared with results from field measurements on real fresco paintings in Casa del Salone Nero and the Villa of the Papyri, Herculaneum, Italy. Copyright © 2014 John Wiley & Sons, Ltd.